CORRELATION BETWEEN SMOKE-FREE AREAS AND SMOKING BEHAVIOR IN INDONESIA - Mohamad Anis Fahmi (Jurnal Berkala Epidemiologi, 2020)
Background: Low public awareness of the impact of smoking makes the implementation of smoke-free areas (KTR) difficult. Smoke-free areas aim to protect the public from the direct and indirect effects of smoking. Purpose: This study aimed to analyze the correlation between the application of smoke-free areas and the prevalence of active and ex-smokers in Indonesia. Method: This study implemented a cross-sectional design, using secondary data from the Riskesdas 2018 on active and ex-smokers. KTR application data were obtained from the Profile of Non-Communicable Diseases in 2016. A Pearson product-moment test was conducted by a computer application to determine the correlation coefficient (r). This coefficient was used to describe the level of correlation between the two variables; significance was determined as a p value of 5%. Results: This study showed that the average application of KTR throughout Indonesia was 50.83%, active smokers comprised 23.49% of the population, and ex-smokers comprised 4.94%. Most active smokers were in Java and Sumatra, while the majority of ex-smokers were in Java and Sulawesi and the majority of KTR was in Java. This study shows that there is a positive correlation between KTR application and the percentage of ex-smokers (r = 0.46; p value = 0.01). Conclusion: There is a positive correlation between the application of KTR and an increase in ex-smokers. The government needs to increase the application of KTR policies.